Теорема про диференцiювання енергiї багатоатомної системи по координатах атомiв (частина I) - Marushko, I. O. (Publishing house "Academperiodika", 2018)
The theorem asserting that the arbitrary-order derivative of the average energy of a solid with respect to atomic coordinates equals the average value of the corresponding derivative of the potential energy operator with respect to atomic coordinates has been proved. This theorem is a generalization of the well-known Gell-Mann–Feynman theorem, which was proved only for the first derivative of the average energy with respect to atomic coordinates. A necessity insuch a generalization is associated with the calculation of force constants in solids, which are the derivatives of the average energy with respect to atomic coordinates, and, maybe, other physical quantities.